An Inclusive and Integrated Ecocritical Approach in Both Content and Style in Sinan Antoon’s The Book of Collateral Damage (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study offers ecocritical discussions of Sinan Antoon’s The Book of Collateral Damage (2019), focusing on the author’s ecoconsciousness and equitable treatment of all ecological entities. Through a close reading of the novel, this study examines how Antoon develops an inclusive project which traverses the spectrum from anthropocentric to biocentric to ecocentric values, giving value to humans, flora, fauna, air, water, soil, and even artificial environments. Furthermore, it demonstrates how Antoon enlarges his scope of awareness by creating an integrated ecocritical approach in both content and style in his novel. It concludes that Antoon’s thoughtful depiction of an inclusive and integrated eco critical project deserves a place on eco-fiction lists.
Keywords: Anthropocentrism; Anthropomorphism; Biocentrism; Ecocentrism; Ecocriticism